Individual responses of growing pigs to threonine intake - Isola, Renan Di Giovanni [UNESP]; Hauschild, Luciano [UNESP]; Perondi, Dani [UNESP]; Andretta, Ines; Gobi, Jaqueline de Paula [UNESP]; Remus, Aline [UNESP]; Veira, Alini Mari [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2018)
A nitrogen balance test was performed to evaluate the individual responses of growing pigs to threonine intake. Eight commercial barrows were used (body weight ranging from 15 to 20 kg). A dose-response study was performed, in which the threonine supply increased in seven equidistant steps (the seven dietary threonine levels ranged from 50 to 120% of the requirements) every three days for each pig. The levels of all other amino acids were 20% higher than the tested amino acid. Nitrogen retention as a function of threonine intake was calculated per individual and per group (NLIN and NLMixed, respectively) using a linear plateau model. The highest break point value was 42.42 g of threonine intake (the most demanding individual), whereas the lowest value was 34.16 g (the least demanding individual), corresponding to a difference of 19%. In terms of N retention, the highest plateau value was 66.71 g and the lowest was 49.48 g, with a difference of 25%. There was no significant correlation between slope and plateau values or between slope and break point values. When using the model in which all parameters were random effects, the variations in threonine intake and nitrogen retention were 1.68 +/- 1.30 and 0.01 +/- 0.10 g, respectively, and no variance in the slope of the curve was detected. The average daily threonine intake values for the maximum response obtained in the group, as calculated by the NLIN and NLMixed procedures, were 13.96 and 14.02 g/day, respectively. The threonine intake for the maximum N retention between individuals ranged from 34.16 to 42.42 g, corresponding to a difference of 19%. The current recommended intake to optimize N retention is 14.02 g/day. The group responses obtained by the NLMixed procedures are very similar to those estimated by the NLIN procedure (all individuals).
Keywords: amino acids; individuals; nitrogen retention; requirements; variability